Remote sensing applications in environmental and earth system sciences - Dalezios, Nicolas R. (London CRC Press, 2021)
"This book is a contemporary, multi-disciplinary, multi-scaling, updated and upgraded approach of applied remote sensing in the environment. It aims to cover the whole spectrum of current environmental issues related to atmosphere, land, and water. This book starts with an overview of remote sensing technology, and then throughout the book, the author explains with many case studies, the types of data that can be used and the image processing and analysis methods that can be applied to each type of application. This book is an excellent resource for anyone who is interested in remote sensing technologies and their use in Earth systems, natural resources, and environmental science"--
Includes bibliographical references.
Keywords: Environmental sciences; Earth sciences